Just-in-Case Inventories : A Cross-Country Analysis - Guasch, J. Luis; Kogan, Joseph (World Bank, Washington, DC, 2014)
The authors find that raw materials inventories in the manufacturing sector in the 1970s and 1980s were two to three times higher in developing countries than in the United States, despite the fact that in most developing countries real interest rates were at least twice as high. Those significantly high levels of inventories are a burden and an obstacle to country competitiveness and need to be addressed. Poor infrastructure and ineffective regulation, as well as deficiencies in market development, rather than the traditional factors used in inventory models (such as interest rates and uncertainty), are the main determinants and explain these differences. Cross-country estimations show that a one standard deviation worsening of infrastructure increases raw materials inventories by 11 percent to 37 percent, and a one standard deviation worsening of markets increases raw materials inventories by 18 percent to 37 percent. These findings are robust across a number of different proxies and specifications, including an industry-level specification that controls for fixed country effects.